A Survey of Nosql Database For Analyzing Large Volume Of Data In Big Data Platform - S.Raghav, R; Amudhavel, J; Dhavachelvan, P (International Journal of Engineering and Technology, 2018)
The massive improvement of data in the present era is drastically increased, where millions of data is emerging from variety of applications. Due to this massive flow of data the importance of data becomes a key factor in all applications. In old technology the space occupied by data is very less, but in the present scenario the value of every piece of data plays a vital role. The organization needs some new technology to process large amount of data in an effective way. For that purpose data exploration and visualization systems play a vital role in the Big Data era. It is a complex task for the companies to explore and visualize very large datasets. Every company should follow some protocol to have accurate insight from analysis of large volume of data. This strategy helps organizations to enhance their business functionalities and it also helps to identify the way to improve the quality of their products. The big data [25-29] contains some unique databases to handle massive volume of data. In this survey, we explain the characteristics of database and challenges. It also describes about the different techniques and tools currently used for handling large sets of data and their capabilities to support massive volume of data from variety of data sources.Â Â